Osmanlı teşkîlât ve kıyâfet-i askeriyyesi (Osmanlı ordusunun bidâyet-i teessüsünden zamanımıza kadar). - Mahmud Şevket Paşa, 1856-1913. ([İstanbul])
1. c. ([6], 92, [1] sayfa, [19] yaprak resim (renkli))